COMMUNITY MENTAL HEALTH - M.H. Saheb-Zamani (Tehran University of Medical Sciences, 1972)
Twenty to twenty-five years ago, the Community Mental Health Center (CHMC), had scarcely been heard of. Today, it is indeed a movement, and apparently widespread. A total of ten services considered to be necessary to provide adequate mental health services: (1) in patient, (2) out-patient, (3) partial hospitalization, (4) emergency, (5) consultation, (6) diagn1ostic, (7) rehabilitative, (8) precare and aftercare, (9) training, (10) research and evaluation services. This Concept of Community Mental Health would include as many community agents as possible in co-operative efforts. To the average educated layman, and, unfortunately to most mental health practitioners the community mental health care has become synonymous with the provision of mere psycho-therapy. The community mental health center has not succeeded in becoming inductor of catalytic agent in the growth of its patients, nor has it become significantly involved with the community as a scrcla1 system. These are grim facts. But new hope has begun to appear. It is contained in four revolutions now under way - revolutions in understanding, in research, in nu1ternal and child care and in education for mental health.